INVESTIGATION OF ELECTROMAGNETIC FIELD VALUES IN MEDIUM VOLTAGE TRANSFORMER SUBSTATION - Kosalay, Ilhan; Inan, Aslan (YILDIZ TECHNICAL UNIV, 2007)
Power plants, transformer substations, transmission lines and similar power system equipments produce power frequency electromagnetic fields in near area when they are working in normal operating condition. Studies about possible negative effects of electromagnetic fields due to electrical installations on living creature have just gone on. In this study, firstly researchers related to this subject are mentioned then explicating of measurements that is carried out in a sample distribution substation is done and magnetic field values at the measurement points are calculated by customized software. Measurement values are encountered with the standards and at conclusion, some suggestions are given.
Keywords: Transformer substations; electromagnetic field; ICNIPR limit values; MAGNETIC-FIELD; INTERFERENCE; Engineering